Crowning Metal Ions by Supramolecularization as a General Remedy toward a Dendrite‐Free Alkali‐Metal Battery. Issue 31 (19th June 2021) - Lu, Ziyang; Guo, Yong; Zhang, Siwei; Wu, Shichao; Meng, Rongwei; Hong, Shuang; Li, Jiaxi; Xue, Haoyu; Zhang, Boyi; Fan, Dinghui; Zhang, Yifang; Zhang, Chen; et al.
Abstract: Alkali metals have low potentials and high capacities, making them ideal anodes for next‐generation batteries, but they suffer major problems, including dendrite growth and low Coulombic efficiency (CE). Achieving uniform metal deposition and having a reliable solid electrolyte interphase (SEI) are the basic requirements for overcoming these problems. Here, a general remedy is reported for various alkali‐metal anodes by the supramolecularization of alkali‐metal cations with crown ethers that follows a size‐matching rule. The positively charged supramolecular complex provides electrostatic shielding layers to regulate metal deposition and suppress dendrite formation. More promisingly, it reforms electric double layers and drives the production of organic‐dominated SEIs with improved flexibility that can accommodate large volume changes. The high flexibility of SEIs during metal deposition and dissolution reduces the amount of dead metal and improves CE and cycling stability. Specifically, a 200% excess Li‐based full cell has a capacity retention of ≈100% after 100 cycles. This crown‐like supramolecularization strategy is a new chemistry that may be used for the production of dendrite‐free metal‐anode‐based batteries not limited to the cases with alkali metal. It is also expected as a practical technology to improve the uniformity of coatings produced in the electrodeposition industry. Abstract : A general supramolecularization strategy with size‐matching crown ethers is proposed to protect alkali‐metal anodes (Li, Na, and K). The unique electrostatic shielding layer and organic‐dominated solid electrolyte interphase (SEI) induced by the crown ether–Li + /Na + /K + assembly effectively inhibit the growth of alkali‐metal dendrites and largely improve the lifespan of alkali‐metal batteries.